Post-socialist societal trajectories: democratic and market transition or state capture? - Nonchev, Andrey (Research Papers, 2018)
The article discusses alternative trajectories of post-socialist societal transformations, with an emphasis on a specific state of society designated as "state capture". It presents a theoretical model that interprets the state capture not as an anonymous actorless process, but as a rational pursuit of specific strategies for acquisition, concentration and preservation of political and economic power and extraction of economic benefits/rents. The implementation of these strategies involves the formation and operation of the politico-economic power networks that seek to control key public legislative, executive and judiciary institutions. These processes have a systematic nature and significant political, economic and social consequences.
Keywords: State capture; Public institutions; Politico-economic power networks; Clientelism; Corruption